Effects of support on Ni-based catalysts for dry reforming of methane - Sardar Ali (20837642) (2025)
We report the development and evaluation of Ni-based catalysts supported on La2O3, ZrO2, and Al2O3 for dry methane reformation. The catalysts were synthesized using the solution combustion synthesis (SCS) method, characterized using several cutting-edge analytical tools, and tested for CO2 reformation of methane in a fixed bed plug-flow reactor. Catalytic activity and physicochemical properties of the studied catalysts varied considerably, indicating that the nature of support had a considerable impact. The Ni/Al2O3 nanocatalyst outperformed the Ni/La2O3 and Ni/ZrO2 catalysts in terms of catalytic activity and stability during the DRM process. During T.O.S. stability tests, the Ni/La2O3 catalyst demonstrated higher initial CH4 conversion (∼95.3 %) than the Ni/Al2O3 catalyst (∼88.7 %). However, after 50 h on stream, the Ni/La2O3 catalyst deactivated significantly, but the Ni/Al2O3 catalyst remained active. Amongst the catalysts tested, the zirconia-supported Ni catalyst had the least activity and demonstrated no activity at temperatures below 800 °C. The analysis of the TPR profile of the Ni/ZrO2 catalyst demonstrated the presence of α-NiO species, indicating a weak metal to support contact, resulting in deactivation due to carbon deposition and aggregation of active sites. The thermogram of the Ni/La2O3 catalyst indicated a combination of two Ni species. The first reduction peak at 342.2 °C occurred by the reduction of α-NiO species. The second reduction peak at 695 °C was caused by the reduction of surface β-NiO species. The absence of δ-NiO species in the La2O3 crystals suggests that Ni2+ did not induce inside the lattice. In contrast, Ni/Al2O3 showed the presence of NiAl2O4 nanocrystallite (δ-NiO) spinel and NiO-Al2O3 solid solution, responsible for high activity and stability. Other Information Published in: Cleaner Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.clce.2025.100201